CANCER AND NEW PROSPECTIVE TO TREAT CANCER - MEHDI, SHIRAZ; CHAUHAN, AYUSH; DHUTTY, AYUSH (International Journal of Current Pharmaceutical Research, 2023)
Cancer is a condition when a few of the body’s cells grow out of control and spread across other bodily regions. In the millions of cells that make up the human body, cancer may develop practically anywhere. Human cells often divide (via a process known as cell growth and multiplication) to create new cells when the body requires them. New cells replace old ones when they die as a result of ageing or injury. Aside from recent significant advancements in stem cell treatment, targeted therapy, ablation therapy, nanoparticles, natural antioxidants, radionics, chemodynamic therapy, sonodynamic therapy, and ferroptosis-based therapy, traditional treatment modalities like surgery, chemotherapy, and radiotherapy are still in use. Oncology practices today concentrate on creating effective and secure cancer nanomedicines. Targeting both primary and metastatic cancer foci, stem cell treatment has demonstrated remarkable success in regenerating and repairing sick or damaged tissues, and nanoparticles have introduced novel diagnostic and therapeutic possibilities. The development and spread of particular cancer cells can be prevented by targeted treatment, which also protects good cells from harm. Ablation treatment has become a less invasive method for freezing or burning tumours without performing open surgery. Natural antioxidants have shown promise in locating free radicals and counteracting their damaging effects, perhaps treating or preventing cancer. Clinical trials are being conducted on a number of innovative technologies, some of which have already received approval. A summary on current developments and discoveries in cancer therapy was provided in this review.